Women's right to the throne: A comparison between the Sultanates of Yogyakarta and Brunei Darussalam - Anom Wahyu Asmorojati; Immawan Wahyudi; Rahmat Muhajir Nugroho; Rofi Aulia Rahman (Jurnal Hukum Novelty, 2026)
Introduction to the Problem: This article examines the issue of gender inequality in royal succession by comparing women's right to ascend the throne in the Sultanate of Yogyakarta and in Brunei Darussalam. While Yogyakarta has begun to open up the discourse on women's succession through the King's Word and constitutional interpretation, Brunei explicitly restricts succession to male heirs under its constitution. Purpose/Study Objectives: The purpose of this article is to analyze and compare the position and rights of women in royal succession within the Sultanate of Yogyakarta and Brunei Darussalam, to identify the cultural, historical, and religious factors that influence this practice, and to evaluate it in the light of international human rights principles, in particular CEDAW. Design/Methodology/Approach: This research uses normative juridical research methods with a comparative approach, focusing on the analysis of legal texts, constitutional provisions, customary regulations, and international human rights instruments. Findings: The study reveal that although both the Sultanate of Yogyakarta and Brunei Darussalam are rooted in patriarchal traditions of royal succession, they diverge significantly in their capacity for legal and normative adaptation. In Yogyakarta, the combination of Sabda Raja, Dawuh Raja, and Constitutional Court Decision No. 88/PUU-XIV/2016 has created a transformative opening that reinterprets customary law in line with constitutional principles and international human rights norms, thereby enabling the possibility of female succession through an evolving model of adaptive legal pluralism. By contrast, Brunei maintains a structurally closed system in which the constitutional requirement of a male ruler (reinforced by the Melayu Islam Beraja ideology and religious authority) institutionalizes gender exclusion and limits interpretive flexibility. This comparison demonstrates that restrictions on women’s leadership are not inherently derived from Islamic doctrine but are shaped by differing configurations of political authority, legal flexibility, and engagement with international norms, with Yogyakarta illustrating the potential for reform and Brunei reflecting the persistence of entrenched patriarchal governance. Paper Type: Research Article